Occupational health and safety in Iran: Accident cost analysis and the importance of education in accident prevention - Gourabi, Hamed Hosseinian (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2011)
ABSTRACT: The aim of this work is to introduce project financing and underlining its importance and application for financing large capital intensive projects, such as infrastructure ones. In order to achieve this purpose, first a brief history of project finance and some distributive statistical findings in different industrial sectors has been presented. Then the financial model of a single cycle power plant being given to an independent power producer is built and its results reported. In the next step, different categories of associated risk to this private power plant project are being identified, the critical variables captured and the risk simulated. Ultimately, risk mitigation is considered by studying and recommending right type of contracts as far as possible. Keywords: Project finance, power plant, risk, contract. ………………………………………………………………………………………………………………………… ÖZ: Bu çalışmanın amacı proje finansmanı, önemi ve büyük sermayeli projelerin finansmanını tanıtmaktır. Örneğin altyapı projeleri. Bu amaca ulaşmak için ilk olarak proje finansmanının kısa tarihçesi ve farklı endüstriyel sektörlerde bazı dağıtımsal istatistiksel bulgular sunulmuştur. Daha sonra tek çevrim santrali için kurulan finansal model ve sonuçları rapor edilmiştir. Bir sonraki adımda özel güç santrali projesinin farklı kategorilerde ilişkili riskleri ve riskli değişkenleri tanımlanmış ve risk simule edilmiştir. Sonuç olarak, risk azaltma mümkün olduğunca doğru tipte sözleşmeleri çalışarak ve tavsiye ederek sağlanmıştır. Anahtar Kelimeler: Proje finansmanı, enerji santrali, risk, sözleşme.
Master of Science in Industrial Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2011. Supervisor: Assist. Prof. Dr. Emine Atasoylu.
Keywords: Industrial Engineering; Industrial accidents - Iran; Industrial safety - Workers Education - Iran; Occupational Accidents Injury Accidents Prevention Job Training Direct Cost indirect Cost